Loop Ileostomy Closure as an Overnight Procedure: Institutional Comparison With the National Surgical Quality Improvement Project Data Set. Issue 8 (August 2017) - Berger, Nicholas G.; Chou, Raymond; Toy, Elliot S.; Ludwig, Kirk A.; Ridolfi, Timothy J.; Peterson, Carrie Y.
Abstract : BACKGROUND: Enhanced recovery pathways have decreased length of stay after colorectal surgery. Loop ileostomy closure remains a challenge, because patients experience high readmission rates, and validation of enhanced recovery pathways has not been demonstrated. This study examined a protocol whereby patients were discharged on the first postoperative day and instructed to advance their diet at home with close telephone follow-up. OBJECTIVE: The hypothesis was that patients can be safely discharged the day after loop closure, leading to shorter length of stay without increased rates of readmission or complications. DESIGN: Patients undergoing loop ileostomy closure were queried from the American College of Surgeons National Surgical Quality Improvement Project and compared with a single institution (2012–2015). Length of stay, 30-day readmission, and 30-day morbidity data were analyzed. SETTINGS: The study was conducted at a tertiary university department. PATIENTS: The study includes 1602 patients: 1517 from the National Surgical Quality Improvement Project database and 85 from a single institution. MAIN OUTCOME MEASURES: Length of stay and readmission rates were measured. RESULTS: Median length of stay was less at the single institution compared with control (2 vs 4 d; p < 0.001). Thirty-day readmission (15.3% vs 10.4%; p = 0.15) and overall 30-day complications (15.3% vs 16.7%; p = 0.73) were similar between cohorts. Estimated adjusted length of stay was less in the single institution (2.93 vs 5.58 d; p < 0.0001). There was no difference in the odds of readmission ( p = 0.22). LIMITATIONS: The main limitations of this study include its retrospective nature and limitations of the National Surgical Quality Improvement Program database. CONCLUSIONS: Next-day discharge with protocoled diet advancement and telephone follow-up is acceptable after loop ileostomy closure. Patients can benefit from decreased length of stay without an increase in readmission or complications. This has the potential to change the practice of postoperative management of loop ileostomy closure, as well as to decrease cost.See Video Abstract athttp://links.lww.com/DCR/A310 .